High‐temperature stabilization of polypropylene using hindered phenol–thioester stabilizer combinations, Part 2: Optimization and efficacy via encapsulation with silicate fillers. Issue 2 (2nd February 2021) - Allen, Norman S.; Jones, Andrew P.; Liauw, Christopher M.; Edge, Michele; Keck‐Antoine, Klaus; Yeo, Joeng‐Ho
Abstract: The thermal degradation of unstabilized polypropylene has been investigated under long‐term thermal aging at 150°C, with additive concentration studies on combinations of an established hindered phenolic antioxidant (pentaerythritol tetrakis (3‐(3, 5‐di‐tert‐butyl‐4‐hydroxyphenyl) propionate) [S1010] and two popular thioesters (distearyl‐3, 3′‐thiodipropionate [DSTDP] and didodecyl‐3, 3′‐thiodipropionate [DLTDP]) using melt flow rate (MFR), carbonyl index (Fourier transform spectroscopy [FTIR]) and differential scanning calorimetry (DSC) (oxidation induction time [OIT]) and ultimate embrittlement time (fracture) on injection‐molded test pieces. It was found in part 1 that 20:80 phenol:thioester ratios provided the best long‐term thermal stability (LTTS). Part 2 investigates potential improvements in stabilization, involving the use of controlled release systems in which the stabilizers are melt blended in the PP together with high surface area inorganic substrates. Here, a calcined gel silica SD3128 and two layered silicates Rockwood Additives Fulcat® 800 and Laponite® B were incorporated into the polymer formulations in order to limit stabilizer mobility at 6000 ppm through potential surface adsorption and subsequent controlled release. Additional hindered amine light stabilizers were also added as long‐term heat stabilizers and to act as displacing agents that promote controlled release via competitive adsorption on processing due to the strongly adsorbing amine functionalities. In some instances, the LTTS showed improvement. Flow micro calorimetry was used to investigate the stabilizer–substrate interactions. It was found that as a result of its small pore structure, Laponite B could only adsorb smaller molecules such as that of DLTDP while Fulcat® 800 was a more strongly adsorbing substrate with larger pores able to accommodate even the largest of the hindered amine light stabilizer (HALS) molecules. The gel silica SD3128 had overall the most adsorbing ability with each of these characteristics supporting the aging data studied in parallel. The data are discussed in relation to the long‐term stabilization of polypropylene in high‐temperature applications such as under the bonnet of automobiles where minimizing stabilizer losses and maximizing synergy are important. Abstract : Structural representation of a montmorillonite smectite exhibiting layers of clay in a stacking configuration with a layer of exchangeable cations between each layer trapping and adsorbing competitively different stabilizers giving enhanced LTTS in Polypropylene.